Exploring Tradeoffs between Specialized Kernels and a Reusable Overlay in a Stereo-Matching Case Study - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (International Journal of Reconfigurable Computing (IJRC))
FPGAs are known to permit huge gains in performance and efficiency for suitable applications but still require reduced design efforts and shorter development cycles for wider adoption. In this work, we compare the resulting performance of two design concepts that in different ways promise such increased productivity. As common starting point, we employ a kernel-centric design approach, where computational hotspots in an application are identified and individually accelerated on FPGA. By means of a complex stereo matching application, we evaluate two fundamentally different design philosophies and approaches for implementing the required kernels on FPGAs. In the first implementation approach, we designed individually specialized data flow kernels in a spatial programming language for a Maxeler FPGA platform; in the alternative design approach, we target a vector coprocessor with large vector lengths, which is implemented as a form of programmable overlay on the application FPGAs of a Convey HC-1. We assess both approaches in terms of overall system performance, raw kernel performance, and performance relative to invested resources. After compensating for the effects of the underlying hardware platforms, the specialized dataflow kernels on the Maxeler platform are around 3x faster than kernels executing on the Convey vector coprocessor. In our concrete scenario, due to trade-offs between reconfiguration overheads and exposed parallelism, the advantage of specialized dataflow kernels is reduced to around 2.5x.

Easy-to-Use On-The-Fly Binary Program Acceleration on Many-Cores - Damschen, Marvin; Plessl, Christian (Proceedings of the 5th International Workshop on Adaptive Self-tuning Computing Systems (ADAPT))
This paper introduces Binary Acceleration At Runtime(BAAR), an easy-to-use on-the-fly binary acceleration mechanismwhich aims to tackle the problem of enabling existentsoftware to automatically utilize accelerators at runtime. BAARis based on the LLVM Compiler Infrastructure and has aclient-server architecture. The client runs the program to beaccelerated in an environment which allows program analysisand profiling. Program parts which are identified as suitable forthe available accelerator are exported and sent to the server.The server optimizes these program parts for the acceleratorand provides RPC execution for the client. The client transformsits program to utilize accelerated execution on the server foroffloaded program parts. We evaluate our work with a proofof-concept implementation of BAAR that uses an Intel XeonPhi 5110P as the acceleration target and performs automaticoffloading, parallelization and vectorization of suitable programparts. The practicality of BAAR for real-world examples is shownbased on a study of stencil codes. Our results show a speedup ofup to 4 without any developer-provided hints and 5.77 withhints over the same code compiled with the Intel Compiler atoptimization level O2 and running on an Intel Xeon E5-2670machine. Based on our insights gained during implementationand evaluation we outline future directions of research, e.g.,offloading more fine-granular program parts than functions, amore sophisticated communication mechanism or introducing onstack-replacement.

Improving Packet Processing Performance in the ATLAS FELIX Project – Analysis and Optimization of a Memory-Bounded Algorithm - Schumacher, Jörn; T. Anderson, J.; Borga, A.; Boterenbrood, H.; Chen, H.; Chen, K.; Drake, G.; Francis, D.; Gorini, B.; Lanni, F.; Lehmann-Miotto, Giovanna; Levinson, L.; et al. (Proc. Int. Conf. on Distributed Event-Based Systems (DEBS))

Aktuelles Schlagwort: Approximate Computing - Plessl, Christian; Platzner, Marco; Schreier, Peter J. (Informatik Spektrum)
Keywords: approximate computing; survey

Transparent offloading of computational hotspots from binary code to Xeon Phi - Damschen, Marvin; Riebler, Heinrich; Vaz, Gavin Francis; Plessl, Christian (Proceedings of the 2015 Conference on Design, Automation and Test in Europe (DATE))
In this paper, we study how binary applications can be transparently accelerated with novel heterogeneous computing resources without requiring any manual porting or developer-provided hints. Our work is based on Binary Acceleration At Runtime (BAAR), our previously introduced binary acceleration mechanism that uses the LLVM Compiler Infrastructure. BAAR is designed as a client-server architecture. The client runs the program to be accelerated in an environment, which allows program analysis and profiling and identifies and extracts suitable program parts to be offloaded. The server compiles and optimizes these offloaded program parts for the accelerator and offers access to these functions to the client with a remote procedure call (RPC) interface. Our previous work proved the feasibility of our approach, but also showed that communication time and overheads limit the granularity of functions that can be meaningfully offloaded. In this work, we motivate the importance of a lightweight, high-performance communication between server and client and present a communication mechanism based on the Message Passing Interface (MPI). We evaluate our approach by using an Intel Xeon Phi 5110P as the acceleration target and show that the communication overhead can be reduced from 40% to 10%, thus enabling even small hotspots to benefit from offloading to an accelerator.

FELIX: a High-Throughput Network Approach for Interfacing to Front End Electronics for ATLAS Upgrades - Anderson, J; Borga, A; Boterenbrood, H; Chen, H; Chen, K; Drake, G; Francis, D; Gorini, B; Lanni, F; Lehmann Miotto, G; Levinson, L; Narevicius, J; et al. (Journal of Physics: Conference Series)
The ATLAS experiment at CERN is planning full deployment of a new unified optical link technology for connecting detector front end electronics on the timescale of the LHC Run 4 (2025). It is estimated that roughly 8000 GBT (GigaBit Transceiver) links, with transfer rates up to 10.24 Gbps, will replace existing links used for readout, detector control and distribution of timing and trigger information. A new class of devices will be needed to interface many GBT links to the rest of the trigger, data-acquisition and detector control systems. In this paper FELIX (Front End LInk eXchange) is presented, a PC-based device to route data from and to multiple GBT links via a high-performance general purpose network capable of a total throughput up to O(20 Tbps). FELIX implies architectural changes to the ATLAS data acquisition system, such as the use of industry standard COTS components early in the DAQ chain. Additionally the design and implementation of a FELIX demonstration platform is presented and hardware and software aspects will be discussed.

Einleitung: Organisationen und Konventionen - Knoll, Lisa (Organisationen und Konventionen)

Organisationen und Konventionen. Die Soziologie der Konventionen in der Organisationsforschung

The Hidden Regulation of Carbon Markets - Knoll, Lisa (Historical Social Research)

MiLeNa – ein überregionales Programm zur MINT-Lehrernachwuchsförderung - Salinga, Christian; Heinke, Heidrun; Jonas-Ahrend, Gabriela; Theyßen, Heike; Bahr, Ursula; Erb, Roger

Einrichten - Bartz, Christina (Historisches Wörterbuch des Mediengebrauchs)

Bewertungsfernsehen - Bartz, Christina (Pop. Kultur & Kritik H. 7)

Kriegsausbruch, Kriegs Ausbruch, KriegsAusbruch: About the possible connection between linguistic variety and age, based on personal journals from 1892-1944 - Schuster, Britt-Marie (The lifespan perspective)
Keywords: Kommunikationsgeschichte

Wie geht’s (Dir)? Zur diachronen Entwicklung pragmatischer Phraseme im kontrastiven Vergleich - Schuster, Britt-Marie (Sektion A1. Beziehungsgestaltung durch Sprache. Akten des XIII. Internationalen Germanistenkongresses Shanghai 2015. Germanistik zwischen Tradition und Innovation (Publikationen der Internationalen Vereinigung für Germanistik (IVG)))
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Einfachheit, Wiederholung und Kontrast: Zur Konstanz sprachlicher Verfahren in der persuasiven Kommunikation - Schuster, Britt-Marie (Wirksame Rede im Frühneuhochdeutschen: Syntaktische und textstilistische Aspekte)
Keywords: Kommunikationsgeschichte

Wirksame Rede im Frühneuhochdeutschen: Syntaktische und textstilistische Aspekte - Schuster, Britt-Marie; Dogaru, Dana
Keywords: Kommunikationsgeschichte

Aligning training models with smartphone properties in WiFi fingerprinting based indoor localization - Hoang, Manh Kha; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (40th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2015))

„Unwälzbar ist der Stein ,es war': ewig müssen auch alle Strafen sein!" - Corall, Niklas (Nietzscheforschung)
Keywords: General Engineering

Heilige Wesen - Lebewesen - Corall, Niklas (Nietzscheforschung)
Keywords: General Engineering

Organizations, Climate Change, and Transparency - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank (Organization & Environment)
The debate surrounding climate change often centers on companies’ contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

The Philosophy of the Marburg Neo-Kantians - Luft, Sebastian (New Approaches to Neo-Kantianism)

Next Generation, Secure Cloud-based Pan-European Information System for Enhanced Disaster Awareness for Crisis Response and Management - Kuhnert, Maike; Wietfeld, Christian; Paterour, Olivier; Georgiev, Alexander; Petersen, Katrina; Büscher, Monika; Pottebaum, Jens (12th Proceedings of the International Conference on Information Systems for Crisis Response and Management, Krystiansand, Norway, May 24-27, 2015)
Keywords: Ver{\

Designing with Users: Co-Design for Innovation in Emergency Technologies for Crisis Response and Management - Petersen, Katrina; Büscher, Monika; Kuhnert, Maike; Schneider, Steffen; Pottebaum, Jens (12th Proceedings of the International Conference on Information Systems for Crisis Response and Management, Krystiansand, Norway, May 24-27, 2015)
Keywords: Ver{\

Additive Manufacturing for Future Repair and Maintenance for the Aerospace Industry - Pottebaum, Jens; Lindemann, Christian-Friedrich; Deppe, Gereon; Koch, Rainer (Aviation in Europe - Innovating for Growth, Proceedings of the Sventh European Aeronautics Days)

Geschichte schreibend lernen - Hartung, Olaf (Schreiben als Lernen. Kompetenzentwicklung durch Schreiben (in allen Fächern))

Generisches Geschichtslernen. Drei Aufgabentypen im Vergleich - Hartung, Olaf (Zeitschrift für Geschichtsdidaktik)

Die "sich ewig wiederholende Arbeit" des Geschichtsbewusstseins - Sprache als Medium des historischen Lernens - Hartung, Olaf (Zeitschrift für Geschichtsdidaktik)

Lehrkompetenzen in der wissenschaftlichen Weiterbildung, Konzepte, Forschungsansätze und Anwendungen

Puzzling History. The Fragments of Fabius Pictor - Moritz, Tilman (Ancient Warfare Magazine)

Cross-cutting organizational and demographic divides and the performance of research and development teams: two wrongs can make a right - Iseke, Anja; Kocks, Birgit; Schneider, Martin; Schulze-Bentrop, Conrad (R&D Management)

Ein literarischer ›Versuch‹ im Experimentierfeld Zeitschrift. Medieneffekte der Deutschen Rundschau auf Gottfried Kellers Sinngedicht - Gretz, Daniela (ZfdPh)

Raman scattering efficiency in LiTaO3 and LiNbO3 crystals - Sanna, Simone; Neufeld, Sergej; Rüsing, Michael; Berth, Gerhard; Zrenner, Artur; Schmidt, Wolf Gero (Physical Review B)
LiTaO3 and LiNbO3 crystals are investigated here in a combined experimental and theoretical study that uses Raman spectroscopy in a complete set of scattering geometries and corresponding density-functional theory calculations to provide microscopic information on their vibrational properties. The Raman scattering efficiency is computed from first principles in order to univocally assign the measured Raman peaks to the calculated eigenvectors. Measured and calculated Raman spectra are shown to be in qualitative agreement and confirm the mode assignment by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)], thus finally settling a long debate. While the two crystals show rather similar vibrational properties overall, the E-TO9 mode is markedly different in the two oxides. The deviations are explained by a different anion-cation bond type in LiTaO3 and LiNbO3 crystals.

Can service learning foster a social responsibility among students? – A didactical analysis and empirical case-study in business education at a German university - Gerholz, Karl-Heinz; Losch, Simone (Corporate Social Responsibility: Locating the Missing Link)

An Overview of Topic Discovery in Twitter Communication through Social Media Analytics - Chinnov, Andrey; Kerschke, Pascal; Meske, Christian; Stieglitz, Stefan; Trautmann, Heike (Proceedings of the 20$^th$ Americas Conference on Information Systems (AMCIS ’15))
The need for automatic methods of topic discovery in the Internet grows exponentially with the amount of available textual information. Nowadays it becomes impossible to manually read even a small part of the information in order to reveal the underlying topics. Social media provide us with a great pool of user generated content, where topic discovery may be extremely useful for businesses, politicians, researchers, and other stakeholders. However, conventional topic discovery methods, which are widely used in large text corpora, face several challenges when they are applied in social media and particularly in Twitter – the most popular microblogging platform. To the best of our knowledge no comprehensive overview of these challenges and of the methods dedicated to address these challenges does exist in IS literature until now. Therefore, this paper provides an overview of these challenges, matching methods and their expected usefulness for social media analytics.

Detecting Funnel Structures by Means of Exploratory Landscape Analysis - Kerschke, Pascal; Preuss, Mike; Wessing, Simon; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO ’15))
In single-objective optimization different optimization strategies exist depending on the structure and characteristics of the underlying problem. In particular, the presence of so-called funnels in multimodal problems offers the possibility of applying techniques exploiting the global structure of the function. The recently proposed Exploratory Landscape Analysis approach automatically identifies problem characteristics based on a moderately small initial sample of the objective function and proved to be effective for algorithm selection problems in continuous black-box optimization. In this paper, specific features for detecting funnel structures are introduced and combined with the existing ones in order to classify optimization problems regarding the funnel property. The effectiveness of the approach is shown by experiments on specifically generated test instances and validation experiments on standard benchmark problems.

Evaluation of a Multi-Objective EA on Benchmark Instances for Dynamic Routing of a Vehicle - Meisel, Stephan; Grimme, Christian; Bossek, Jakob; Wölck, Martin; Rudolph, Guenter; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO ’15))
We evaluate the performance of a multi-objective evolutionary algorithm on a class of dynamic routing problems with a single vehicle. In particular we focus on relating algorithmic performance to the most prominent characteristics of problem instances. The routing problem considers two types of customers: mandatory customers must be visited whereas optional customers do not necessarily have to be visited. Moreover, mandatory customers are known prior to the start of the tour whereas optional customers request for service at later points in time with the vehicle already being on its way. The multi-objective optimization problem then results as maximizing the number of visited customers while simultaneously minimizing total travel time. As an a-posteriori evaluation tool, the evolutionary algorithm aims at approximating the related Pareto set for specifically designed benchmarking instances differing in terms of number of customers, geographical layout, fraction of mandatory customers, and request times of optional customers. Conceptional and experimental comparisons to online heuristic procedures are provided.

Improving the State of the Art in Inexact TSP Solving Using Per-Instance Algorithm Selection - Kotthoff, Lars; Kerschke, Pascal; Hoos, Holger; Trautmann, Heike (Learning and Intelligent Optimization)
We investigate per-instance algorithm selection techniques for solving the Travelling Salesman Problem (TSP), based on the two state-of-the-art inexact TSP solvers, LKH and EAX. Our comprehensive experiments demonstrate that the solvers exhibit complementary performance across a diverse set of instances, and the potential for improving the state of the art by selecting between them is significant. Using TSP features from the literature as well as a set of novel features, we show that we can capitalise on this potential by building an efficient selector that achieves significant performance improvements in practice. Our selectors represent a significant improvement in the state-of-the-art in inexact TSP solving, and hence in the ability to find optimal solutions (without proof of optimality) for challenging TSP instances in practice.

R2 Indicator Based Multiobjective Search - Brockhoff, D; Wagner, T; Trautmann, Heike (Evolutionary Computation Journal)
In multiobjective optimization, set-based performance indicators are commonly used to assess the quality of a Pareto front approximation. Based on the scalarization obtained by these indicators, a performance comparison of multiobjective optimization algorithms becomes possible. The R2 and the Hypervolume (HV) indicator represent two recommended approaches which have shown a correlated behavior in recent empirical studies. Whereas the HV indicator has been comprehensively analyzed in the last years, almost no studies on the R2 indicator exist. In this extended version of our previous conference paper, we thus perform a comprehensive investigation of the properties of the R2 indicator in a theoretical and empirical way. The influence of the number and distribution of the weight vectors on the optimal distribution of µ solutions is analyzed. Based on a comparative analysis, specific characteristics and differences of the R2 and HV indicator are presented. Furthermore, the R2 indicator is integrated into an indicator-based steady-state evolutionary multiobjective optimization algorithm (EMOA). It is shown that the so-called R2-EMOA can accurately approximate the optimal distribution of µ solutions regarding R2.

Multi-Objective Analysis of Approaches to Dynamic Routing Of a Vehicle - Grimme, C; Meisel, S; Trautmann, Heike; Rudolph, G; Wölck, M (Proceedings of the European Conference On Information Systems)
We consider a routing problem for a single vehicle serving customer Locations in the course of time. A subset of these customers must necessarily be served, while the complement of this subset contains dynamic customers which request for service over time, and which do not necessarily need to be served. The decision maker’s conflicting goals are serving as many customers as possible as well as minimizing total travel distance. We solve this bi-objective Problem with an evolutionary multi-objective algorithm in order to provide an a-posteriori evaluation tool for enabling decision makers to assess the single objective solution strategies that they actually use in real-time. We present the modifications to be applied to the evolutionary multi-objective algorithm NSGA2 in order to solve the routing problem, we describe a number of real-time single-objective solution strategies, and we finally use the gained efficient trade-off solutions of NSGA2 to exemplarily evaluate the real-time strategies. Our results show that the evolutionary multi-objective approach is well-suited to generate benchmarks for assessing dynamic heuristic strategies. Our findings point into future directions for designing dynamic multi-objective approaches for the vehicle routing problem with time windows.

Analyzing the BBOB Results by Means of Benchmarking Concepts - Mersmann, O; Preuss, M; Trautmann, Heike; Bischl, B; Weihs, C (Evolutionary Computation Journal)
We present methods to answer two basic questions that arise when benchmarking optimization algorithms. The first one is: which algorithm is the "best" one? and the second one is: which algorithm should I use for my real-world problem? Both are connected and neither is easy to answer. We present a theoretical framework for designing and analyzing the raw data of such benchmark experiments. This represents a first step in answering the aforementioned questions. The 2009 and 2010 BBOB benchmark results are analyzed by means of this framework and we derive insight regarding the answers to the two questions. Furthermore, we discuss how to properly aggregate rankings from algorithm evaluations on individual problems into a consensus, its theoretical background and which common pitfalls should be avoided. Finally, we address the grouping of test problems into sets with similar optimizer rankings and investigate whether these are reflected by already proposed test problem characteristics, finding that this is not always the case.

Testing vs. building accounting theory with experimental research: insights from management research - Reimsbach, Daniel; Hauschild, Bastian (International Journal of Behavioural Accounting and Finance)
Keywords: Geology; Ocean Engineering; Water Science and Technology

Effects of bandwidth feedback on the automatization of an arm movement sequence - Agethen, Manfred; Krause, Daniel (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

The Neo-Kantian Reader

Philosophical Historiography in Marburg Neo-Kantianism: The Example of Cassirer’s Erkenntnisproblem (The Problem of Knowledge) - Luft, Sebastian (From Hegel to Windelband. Historiography of Philosophy in the 19th Century)

Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung. - Beutner, Marc; Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

The Philosophy of Ernst Cassirer: A Novel Assessment

Die Modulwerkstatt – Lehrkompetenzentwicklung in der Weiterbildung für die Weiterbildung - Hartung, Olaf (Lehrkompetenzen in der wissenschaftlichen Weiterbildung, Konzepte, Forschungsansätze und Anwendungen)

Aktuelle Trends in der Museumsdidaktik und ihre Bedeutung für das historische Lernen - Hartung, Olaf (Geschichtskultur. Die Anwesenheit von Vergangenheit in der Gegenwart)

Schreiben - Hartung, Olaf (Geschichts-Methodik: Handbuch für die Sekundarstufe I und II)

Ministry of Planning - Schulze, Max